Anomalous Exciton Quenching in Organic Semiconductors in the Low-Yield Limit - Ardalan Armin (The Journal of Physical Chemistry Letters, 2018)
The dynamics of exciton quenching are critical to the operational performance of organic optoelectronic devices, but their measurement and elucidation remain ongoing challenges. Here, we present a method for quantifying small photoluminescence quenching efficiencies of organic semiconductors under steady-state conditions. Exciton quenching efficiencies of three different organic semiconductors, PC70BM, P3HT, and PCDTBT, are measured at different bulk quencher densities under continuous low-irradiance illumination. By implementing a steady-state bulk-quenching model, we determine exciton diffusion lengths for the studied materials. At low quencher densities we find that a secondary quenching mechanism is in effect, which is responsible for approximately 20% of the total quenched excitons. This quenching mechanism is observed in all three studied materials and exhibits quenching volumes on the order of several thousand cubic nanometers. The exact origin of this quenching process is not clear, but it may be indicative of delocalized excitons being quenched prior to thermalization.